2008
DOI: 10.1016/j.rmed.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of the Buteyko technique as an adjunct to conventional management of asthma

Abstract: Six months after completion of the interventions, a large majority of subjects in each group displayed control of their asthma with the additional benefit of reduction in inhaled corticosteroid use in the Buteyko group. The Buteyko technique, an established and widely recognised intervention, or an intensive programme delivered by a chest physiotherapist appear to provide additional benefit for adult patients with asthma who are being treated with inhaled corticosteroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 19 publications
0
42
0
10
Order By: Relevance
“…The contents of the breathing retraining programme in this study were very similar to those in our study, but only face-to-face instruction was investigated and no economic analysis was carried out. A Canadian RCT published in 2008 13 added further support for breathing retraining in asthma, also finding significant reductions in asthma symptoms. In this study, a breathing retraining intervention delivered by physiotherapists in a face-to-face setting was compared with the Butekyo breathing method (also taught in face-to-face sessions by a therapist).…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of the breathing retraining programme in this study were very similar to those in our study, but only face-to-face instruction was investigated and no economic analysis was carried out. A Canadian RCT published in 2008 13 added further support for breathing retraining in asthma, also finding significant reductions in asthma symptoms. In this study, a breathing retraining intervention delivered by physiotherapists in a face-to-face setting was compared with the Butekyo breathing method (also taught in face-to-face sessions by a therapist).…”
Section: Fundingmentioning
confidence: 99%
“…7,8 A number of controlled studies have investigated breathing modification techniques and have reported beneficial outcomes. Breathing control techniques investigated have included the Butekyo breathing method [9][10][11][12][13] and yogic breathing. [14][15][16] Recent studies have shown clinically important effectiveness of physiotherapist-administered breathing exercises for people with asthma in the UK.…”
Section: Trial Registrationmentioning
confidence: 99%
“…Der Medikamentenverbrauch erreichte eine große Verbesserung [26,28,29,37,39]. Er konnte signifikant und klinisch relevant, und wo die Nachhaltigkeit berücksichtigt wurde [28,29], langfristig gesenkt werden.…”
Section: Asthmakontrolle Und Asthmamedikationunclassified
“…Er konnte signifikant und klinisch relevant, und wo die Nachhaltigkeit berücksichtigt wurde [28,29], langfristig gesenkt werden.…”
Section: Asthmakontrolle Und Asthmamedikationunclassified
“…There is a paucity of studies of these treatments, but to date the evidence indicates that none are efficacious (Table 1). [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Outcome of the case Emma is treated every 4 weeks with supervised omalizumab injections at a dosage estimated from the treatment monograph on the basis of her weight (70 kg) and initial immunoglobulin E level: 2 subcutaneous injections of 150 mg each for a total of 300 mg at each visit. After 3 months of this therapy, Emma is no longer experiencing exacerbations.…”
mentioning
confidence: 99%